La prohibición del enriquecimiento injusto de la Administración Pública y el reconocimiento extrajudicial de créditos - Alejandro D. Leiva López (Revista Vasca de Administración Pública)
When the Spanish Administration assumes payment commitments derived from contracts, without having the prior budget or exceeding the preexisting credit, those expenses will be automatically void. However, the invalidity of these contracts could not exempt the Administration from the obligation to compensate those services provided by third parties in good faith, if this avoids the unjust enrichment. For this reason, the extrajudicial recognition of credits was created as an exceptional mechanism that seeks to avoid the unjust enrichment. Therefore, this paper analyzes the legitimacy of this mechanism from the perspective of the theory of unjust enrichment ¿understood as an autonomous source of obligations¿, as well as we also examine the most important Spanish case law disputes about this institution of extrajudicial recognition of credits in recent times.